The reader in al-Jahiz : the epistolary thetoric of an Arabic Prose Master - Hefter, Thomas (United Kingdom : Edinburgh University Press, 2014)
Thomas Hefter takes a new approach in interpreting some of al-Jahiz's'epistolary monographs.' By focussing on the varying ways in which he wrote to the addressee, Hefter shows how al-Jahiz shaped his conversations on the page in order to guide (or manipulate) his actual readers and encourage them to engage with his complex materials
Includes bibliographical references (pages 263-271) and index.
Keywords: al-Jahiz -- -868 or 869 -- Criticism and interpretation; al-Jahiz -- -868 or 869 -- Technique; Books and reading -- Islamic Empire; Arabic literature -- 750-1258 -- History and criticism; Islamic empire -- Intellectual life